2012
DOI: 10.1371/journal.pone.0051491
|View full text |Cite|
|
Sign up to set email alerts
|

Respiratory Viruses in Hospitalized Children with Influenza-Like Illness during the H1n1 2009 Pandemic in Sweden

Abstract: BackgroundThe swine-origin influenza A(H1N1)pdm09 pandemic of 2009 had a slower spread in Europe than expected. The human rhinovirus (HRV) has been suggested to have delayed the pandemic through viral interference. The importance of co-infections over time during the pandemic and in terms of severity of the disease needs to be assessed.ObjectiveThe aim of this study was to investigate respiratory viruses and specifically the presence of co-infections with influenza A(H1N1)pdm09 (H1N1) in hospitalized children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
3
27
0
2
Order By: Relevance
“…19 In our data, coinfections were associated with increased risk of ARI compared with single infections, and they were also associated with more severe disease. However, we did not have sufficient power to fully address how different respiratory viruses interact in the development of ARI, which is of great importance when assessing the potential impact of targeted interventions.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…19 In our data, coinfections were associated with increased risk of ARI compared with single infections, and they were also associated with more severe disease. However, we did not have sufficient power to fully address how different respiratory viruses interact in the development of ARI, which is of great importance when assessing the potential impact of targeted interventions.…”
Section: Discussionsupporting
confidence: 52%
“…[12][13][14][15][16][17] Numerous case series investigating respiratory viruses in hospitalized children with ARI have been published. [18][19][20] However, data are available from only a few case-control studies that examined to what extent specific respiratory viruses cause disease. 12,14,15,21 Furthermore, these studies had limitations in that they used hospital-based control subjects, which might have biased the results.…”
Section: Resultsmentioning
confidence: 99%
“…Note: N = number, CI = confidence interval, GRADE [31] = Grading of Recommendations Assessment, Development and Evaluation, RR = risk ratio, SD = standard deviation, CI = confidence interval.GRADE Working Group grades of evidence. High quality: Further research is very unlikely to change our confidence in the estimate of effect. Moderate quality: Further research is likely to have an important impact on our confidence in the estimate of effect and may change the estimate. Low quality: Further research is very likely to have an important impact on our confidence in the estimate of effect and is likely to change the estimate. Very low quality: We are very uncertain about the estimate.aSerious design limitations: Eight [15], [19], [21], [32], [22], [35], [23] [24] of the eleven studies had serious design limitations including the absence of notification or adjustment for important prognostic factors and the absence of evidence provided on the similarity of co-interventions between both groups.bSerious Inconsistency: There was high statistical heterogeneity ( I 2  = 72%, p<0.001), which was not explained on further subgroup analysis.cSerious indirectness of the comparison: Only three [33] [19] [24] of the eleven studies focused primarily on the comparison of disease severity between single vs viral co-infections.dNo serious imprecision: The assumption of our a priori hypothesis of no difference was met. Cumulative sample size was appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…In a large study conducted in England, co-infection with influenza A virus and HAdV was associated with increased risk of admission to the general ward (14). In a Swedish study, no correlation was observed between the severity of symptoms in children hospitalized with influenza A infection with or without coinfection (27). Consistent with this finding, no difference was found between the severity of influenza A infection and the presence of respiratory viral co-infections in Spain and Brazil (28,29).…”
Section: Discussionmentioning
confidence: 70%